Determination of Cefotaxime in Pharmaceutical Preparations by Visible Spectrophotometry using Methyl Orange and Indigo Carmine Dyes - Bagheri, A.; Ganji, M.D.; Rezvani, M. (Asian Journal of Chemistry, 2011)
A rapid, simple and sensitive validated visible spectrophotometric method has been explained for the assay of cefotaxime in pure form or in pharmaceutical formulations. In this methods, we employed N-bromosuccinimide (NBS) as the oxidimetric reagent and methyl orange and indigo carmine as spectrophotometric reagents. Spectrophotometry involves adding a measured exess of N-bromosuccinimide to cefotaxime in acid medium followed by determination of residual N-bromosuccinimide by reacting with a fixed amount of either methyl orange and measuring the absorbance at 509 nm (method A) or indigo carmine and measuring the absorbance at 608 nm (method B). In both methods, the amount of N-bromosuccinimide reacted corresponds to the amount of cefotaxime. In this methods, the measured absorbance is found to increase linearly with concentration of cefotaxime, which is corroborated by the correlation coefficients of 0.9949 and 0.9935 methyl orange and or indigo carmine, respectively. The system obeys Beer s law for 1.66–10 μg mL-1 and 14.89–44.68 μg mL-1 for method A and method B, respectively. The calculated apparent molar absorptivity values are found to be 1.99 × 104 and 5.44 × 103 L mol cm-1 for method A and method B, respectively. The limits of detection and quantification are also reported for both spectrophotometric methods. The proposed methods were applied successfully to the determination of cefotaxime in commercial vial.